Posture disorders and their causes in rural schools pupils - Radzevičienė,, Liuda; Kazlauskas, Andrius (Social Welfare: Interdisciplinary Approach, 2016)
The aim of the research is to identify the particularities of pupils’ body posture in the rural schools of Šiauliai region. Particularities of pupils’ body posture were screened using Adams forward bend test. It was found out that faulty body posture (lesion of skeleton-muscle system and asymmetry of innervations) is common to the largest part of different age pupils in rural schools. Faulty body posture of asymmetry of innervations has a tendency to normalize during child’s development, and faulty body posture of lesion of skeleton-muscle system might change to serious pathology of bone system.
Keywords: rural schools; school age children; disorders of body posture